2007
DOI: 10.1037/0022-0167.54.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural counseling competencies research: A 20-year content analysis.

Abstract: The authors conducted a 20-year content analysis of the entire field of empirical research on the multicultural counseling competencies (D. W. Sue et al., 1982). They conducted an exhaustive search for empirical research articles using PSYCInfo, as well as complete reviews of the past 20 years of several journals (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
139
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 44 publications
1
139
0
2
Order By: Relevance
“…The utility of a content analysis to understand how various content areas are represented in counseling psychology is a widely accepted approach (see Arredondo et al 2005;Buboltz, Miller and Williams 1999;Carter et al 1998;Miller and Kerlow-Myers 2009;Worthington et al 2008). Content analysis examining internationalization within the field of psychology is also not a new phenomenon.…”
Section: Content Analyses In Counseling Psychologymentioning
confidence: 99%
“…The utility of a content analysis to understand how various content areas are represented in counseling psychology is a widely accepted approach (see Arredondo et al 2005;Buboltz, Miller and Williams 1999;Carter et al 1998;Miller and Kerlow-Myers 2009;Worthington et al 2008). Content analysis examining internationalization within the field of psychology is also not a new phenomenon.…”
Section: Content Analyses In Counseling Psychologymentioning
confidence: 99%
“…Third, content areas were inductively developed by focusing on dependent variables. The content areas used in previous content analysis research were not applicable because they were developed either to review a specific journal (Buboltz et al, 1999) or to study different topics such as multicultural counseling competency (Worthington et al, 2007). Finally, we traced changes in total publications by counting the number of published articles from 1988 to 2009 in 2-year increments.…”
mentioning
confidence: 99%
“…Prior studies using multicultural counseling competence measures found that these instruments measured self-efficacy rather than competence, and also indicated that results may have been influenced by demographics, training variables, and a respondent's worldview (Worthington, Soth-McNett, & Moreno, 2007).…”
Section: Multicultural Counseling Self-efficacymentioning
confidence: 99%
“…Given the emergence of means of assessing counselor characteristics, such as multicultural counseling self-efficacy, conclusions of Worthington et al (2007), and the revised MSJCCs, moving in this new direction seems both timely and professionally responsible. Furthermore, examining the relation between mental illness stigma and multicultural counseling self-efficacy has the potential to add to important areas of study in mental illness stigma, particularly among mental health care providers.…”
Section: Multicultural Counseling Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation